Çocukluk dönemi malignitelerinde kemoterapi sonrası gelişen ön mediyasten kitlesi - (:unkn) unknown (My University, 2001)
Malign hastalıklarda, kemoterapi sonrası ön mediastende kitle gelişimi hem klinisyenler hem de radyologlar için çözülmesi zor bir problemdir. Etyolojide en sık metastatik lenf nodu olmak üzere timus hiperplazisi ve primer hastalık relapsi yer almakta, tanı için invaziv metodlara başvurmak gerekebilmektedir. Hodgkin lenfomada, timik hiperplazi çocukluk ve erişkin yaş grubunda bildirilmekle birlikte, diğer malignitelerde nadirdir. Bilim Dalımızda, Hodgkin Lenfoma (n= 4), Wilms tümörü (n= 1), Abdominal Burkitt lenfoma (n= 1) tanılarıyla kemoterapi sonrası remisyonda izlendikleri dönemde ön mediastende kitle tespit ettiğimiz 6 çocuk hastamizi sunuyoruz. Üç erkek ve 3 kızdan oluşan ve ortalama yaşı 11.4 olan hastalarımızda kemoterapi sonrası, timik hiperplazi saptanma zamanı 3 ay ile 24 ay arasında değişiyordu.

Development of anterior mediastinal mass after chemotherapy in malignant diseases poses a problem both for clinicians and radiologists. Differential diagnosis includes metastatic lymph node involvement, thymus hyperplasia and relaps of the primary disease and invasive methods may need to be utalized for diagnosis. Although thymic hyperplasia has been reported with Hodgkin's disease in children and adults, it can only rarely be observed in other malignancies. Here we report 6 children treated for Hodgkin's disease (n=4), Wilms tumor (n=l) and Burkitt lymphoma (n=l) in whom an anterior mediastinal mass was detected during post-chemotherapy remission period. The median age of our patients was 11.4 years and the time period in which the anterior mediastinal mass was detected ranged from 3 to 24 months.
Anterior mediastinal mass after chemotherapy in pediatric patients with malignancies
Keywords: Hematoloji; Onkoloji; Pediatri